The complete mitochondrial genome of a Green macroalgae species: Ulva meridionalis (Ulvales: Ulvaceae) - Kang, Xinyu (Mitochondrial DNA B Resour, 2020)
Ulva meridionalis, a green macroalgae, is one of the causal species for green tides in Japan and spread into the coast of China. During this research, we sequenced the complete mitochondrial genome of U. meridionalis. The mitogenome is 62,887 bp in length, including 28 encoding genes and 29 tRNA genes. Compared with the Ulva species from mitogenome, the gene order and organization of this mitogenome are similar to most of other determined Ulva mitogenomes, with the nucleotide base composition of A 33.6%, T 32.2%, C 16.2%, and G 18.0%. Phylogenetic analysis shows U. meridionalis is closely related to Ulva flexuosa.